Sovereign Default Risk and Private Sector Access to Capital in Emerging Markets - Das, Udaibir (IMF Working Papers; Working Paper, 2010)
Top down spillovers of sovereign default risk can have serious consequences for the private sector in emerging markets. This paper analyzes the effects of these spillovers using firm-level data from 31 emerging market economies. We assess how sovereign risk affects corporate access to international capital markets, in the form of external credit (loans and bond issuances) and equity issuances. The study first analyzes the impact of sovereign debt crises during the 1980s and 1990s. It goes on to examine the 1993 to 2007 period, using additional measures of sovereign risk-sovereign bond spreads and sovereign ratings-as explanatory variables. Overall, we find that sovereign default risk is a crucial determinant of private sector access to capital, be it external debt or equity. We also find that crisis resolution patterns matter and that defaults towards private creditors have stronger adverse consequences than defaults to official creditors.